Traditional Chinese Medicine diagnostic evaluation of stress symptoms treated by auriculotherapy: a clinical trial - Leonice Fumiko Sato Kurebayashi; Juliana Rizzo Gnatta; Talita Pavarini Borges; Maria Júlia Paes da Silva (Universidade Federal de Goias, 2014)
The objective of this clinical trial was to identify the Traditional Chinese Medicine (TCM) diagnoses for stress symptoms that responded to auriculotherapy. Subjects were 75 nursing professionals of a teaching hospital, with average and high stress scores according to Vasconcelos' List of Stress Symptoms. The subjects were randomized into three groups (control without treatment, auriculotherapy with needles, and auriculotherapy with seeds), treated weekly in the Kidney, Brain stem and Shenmen, for eight sessions. Analysis of variance showed significant differences after treatment (p=0.023) only between the needle and group controls, with 21 symptoms showing differences (p<0.05) in the Student's t-test. In conclusion, auriculotherapy reduced stress with best result for needles than seeds, and the main identified diagnoses were: Stagnation of Qi in the chest, Stagnation of the Liver and the tendinomuscular meridians, Yin Deficiency of the Liver, Kidneys and Xue (Blood). Descriptors: Nursing; Auriculotherapy; Medicine, Chinese Traditional; Diagnosis.